Diurnal changes in serum unconjugated bile acids in normal man. Issue 8 (August 1982) - Setchell, K D; Lawson, A M; Blackstock, E J; Murphy, G M
Abstract : Unconjugated bile acids were measured using gas chromatography-mass spectrometry in the serum of two subjects throughout a 24 hour period and in two other subjects over a six hour period after breakfast. Unconjugated bile acids were found in all samples of serum and included cholic, chenodeoxycholic, deoxycholic, 3 beta, 7 alpha-dihydroxy-5 beta-cholanic (iso-chenodeoxycholic), ursodeoxycholic, 3 beta, 7 beta-dihydroxy-5 beta-cholanic (iso-ursodeoxycholic), 3 beta-hydroxy-5-cholenoic, and lithocholic acids. The maximum concentration of each bile acid generally occurred between breakfast and dinner and total unconjugated bile acid concentrations attained levels of between 2-3 mumol/l. Concentrations increased after breakfast and were often as high as 30-40% of the conjugated bile acid glycocholate, but returned to fasting levels in the absence of lunch. The intestinal absorption of unconjugated bile acids is therefore of greater quantitative importance than was previously thought.